PROBLEMS IN THE MANAGEMENT OF THE ELECTRIC POWER SECTOR IN UZBEKISTAN AND WAYS TO ELIMINATE THEM - Samadovich, Saidov Mash’al (Antis Publisher, 2024)
In this scientific article, the problems in the management of the electricity network, the reforms carried out by the state and their results, the existing problems in the network, the development of electricity by countries of the world, the determination of the features of assessing the effectiveness of Management in the electric power network, the problems in the management of the electric power